Pandangan Tokoh Nahdatul Ulama Tentang Hukum Simpan Pinjam Uang Di Koperasi Guru Kelurahan Simpang Sender Kabupaten OKU Selatan - Rini Masykuro, Yufi Wiyos; Zaharah, Rita; Sari, Novita (ASAS, 2023)
This teacher cooperative has a minimum loan of Rp. 500,000 and a maximum loan of Rp. 10,000,000. In this cooperative system, the interest rate is 10% according to the loan with a repayment period of 10 months. Whereas in Islam forbids interest in every human activity. Ulama here have their own opinion regarding the law of saving and borrowing money in the Simpang Sender Village, OKU Selatan Regency. The role of the Ulama in society is very strong, their opinion will be taken into consideration in the community. This research is a type of field research, and is descriptive in nature. Primary data sources were obtained directly from the research site using the direct interview method with Nahdathul Ulama figures and savings and loan cooperatives in the Simpang Sender Village. Secondary data sources come from several sources, namely journals, books, and the internet related to this research, the data are analyzed qualitatively. Based on the results of the study, it can be concluded that the implementation of saving and borrowing money in the Simpang Sender Village Teacher Cooperative is like cooperatives in general, the funds used to provide loans are the savings funds of members who are members of the cooperative. All members registered in this cooperative are teachers, each member is required to save a minimum of Rp. 10,000 and a maximum of Rp. 100,000. Whereas the views of Nahdatul Ulama figures regarding the practice of Saving and Loans in the Simpang Sender Village Teacher Cooperative have not fulfilled the conditions permitted in Islamic law, where there is still 10% interest in repaying loans paid in installments by members at a time period of 10 months, the interest paid is pay monthly installments of 1% for 10 months.Keywords: cooperative, saving and borrowing money, Nahdatul Ulama figures